Creating an Anxiety Test of Learning English of Dusit Thani College Pattaya Students - Tongkaw, Anurak; Pradujprom, Piyathip; Wongupparaj, Peera (Dusit Thani College Journal, 2020)
This research aimed to create the assessment of English learning anxiety of students at Dusit Thani College, Pattaya and check the properties of the measurement form.The development of measurements, used forward translation and backward translation from the prototype. This research has validity reliability and discrimination checking, for validity checking contains content validity and construct validity for construct validity using the second order confirmatory analysis from 240 samples by using multiple random sampling. The result showed the assessment of English learning anxiety of students at Dusit Thani College, Pattaya consist of anxiety in listening, speaking, reading and writing skills in English language, each aspect of skills is measured by cognitive, somatic and behavioral. This measure had good content validity and good construct validity. This measure has good reliability and good discrimination, with the Cronbach's alpha coefficient of .97 and corrected item-Total correlation of .31-.79. The assessing showed the focus must be on speaking and reading skills first, followed by listening and writing skills respectively. In each skills focus must be on somatic first, followed by behavioral and cognitive respectively.